Peran Pangan Ultra Proses terhadap Peningkatan Risiko Obesitas Anak - Cintawan, Ni Made Karenina Rini Dwi; Graharti, Risti; Sitepu, Ricky Rivalino (CV. Jasa Sukses Abadi, 2026)
The problem of obesity in adolescents has developed into a global health crisis, exacerbated by lifestyle changes and the consumption of ultra-processed foods (UPF). Indonesia is predicted to become one of the countries with the highest cases of childhood obesity, marked by a doubling in the prevalence of adolescent obesity between 2013 and 2018. This literature review aims to comprehensively analyze the role of UPF consumption in increasing the risk of obesity in the child and adolescent population. This study uses a literature review method by searching scientific databases to identify and synthesize articles discussing the relationship between UPF intake and childhood obesity. (Note: The literature search section has been adjusted to focus on UPF and Obesity). Obesity in adolescents is defined based on WHO criteria (BMI/A Z-score >+2 SD) and is classified predominantly as primary obesity (multifactorial). High UPF consumption has been shown to have a positive and significant association with overnutrition; studies show a drastically increased risk of obesity (40% - 66%) in UPF consumers. The etiological mechanisms are multifactorial, including: 1) Energy Balance Disruption (high energy density, poor nutrient profile, fiber deficit); 2) Decreased Thermogenic Effect of Food (TEF) by up to 50; 3) Hormonal Metabolic Disturbances (increased insulin, insulin resistance, changes in brain circuitry); and 4) Exposure to Obesogenic Substances (Endocrine Disruptors) from additives and packaging. Consumption of UPF is a major and complex risk factor for the pathogenesis of childhood and adolescent obesity, acting through metabolic, neurological, and toxicological pathways. Food policy interventions are needed to mitigate these health risks.